2018
DOI: 10.1002/ijc.31334
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acids and risk of melanoma: A Mendelian randomisation analysis

Abstract: Melanoma is the deadliest form of skin cancer, mainly affecting populations of European ancestry. Some observational studies suggest that particular diets reduce melanoma risk, putatively through an increase in polyunsaturated fatty acid (PUFA) consumption. However, interpretation of these observational findings is difficult due to residual confounding or reverse causality. To date, a randomized controlled trial has not been carried out to examine the relationship between PUFAs and melanoma. Hence, we performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…Observational study findings are inconclusive regarding the association of PUFAs and melanoma risk (56,57). Our meta-analyzed results combining the estimates from Liyanage and colleagues (38) suggested that there is no association between PUFAs and melanoma after the adjustment for multiple testing (AA: OR, 1.03; 95% CI, 1.00-1.07; Supplementary Table S6).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Observational study findings are inconclusive regarding the association of PUFAs and melanoma risk (56,57). Our meta-analyzed results combining the estimates from Liyanage and colleagues (38) suggested that there is no association between PUFAs and melanoma after the adjustment for multiple testing (AA: OR, 1.03; 95% CI, 1.00-1.07; Supplementary Table S6).…”
Section: Discussionmentioning
confidence: 72%
“…Similarly, for melanoma, we obtained more precise estimates of OR by combining our study with a previously published study by Liyanage and colleagues (AA, metaanalysis OR, 1.03; 95% CI, 1.00-1.07; ref. 38; Supplementary Table S6). MR estimates for the association of 1 SD increase in PUFAs on common cancers.…”
Section: Mr Analysis Of Pufas On Individual Cancer Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…For the entirety of my candidature, I have also worked on the genetics of other complex traits and outcomes such as addiction, illicit substance use, psychiatric disorders, other malignant cancers and a series of eye-related diseases [156,[339][340][341]. A list of these investigations that were not covered in this thesis was added to Appendix B. I did not expand on any of these projects for several reasons.…”
Section: Application Of Mr In Other Research Areasmentioning
confidence: 99%